Effect of the strut size and tilt angle on the geometric characteristics of selective laser melting AlSi10Mg. Issue 5 (1st June 2021) - Zhang, Baopeng; Han, Xuesong; Chen, Changpeng; Zhang, Wenqi; Liao, Hailong; Chen, Baijin
Abstract : Purpose: The purpose of this study is to investigate the effect of the strut size and tilt angle on the densification behavior, surface roughness and dimensional accuracy of the selective laser melting AlSi10Mg lattice structure was investigated in this study. In this study, the characteristics such as the density, up-skin and down-skin roughness and dimensional accuracy of selective laser melting forming technology manufacturing (SLMed) AlSi10Mg cellular lattice structure were carried. This work reveals the effect of the strut size and tilt angle on the geometric characteristics of SLMed AlSi10Mg and is benefit for controlling the forming performance of the SLMed cellular lattice structure. Design/methodology/approach: Based on AlSi10Mg powder, the influence of the tilt angle changed from 10° to 45° with an increment of 5° were investigated, the influence of the strut size was varied from 0.4 mm to 1.2 mm with an increment of 0.2 mm were investigated. The characteristics such as the density, up-skin and down-skin roughness, dimensional accuracy and mechanical properties of SLM-ed AlSi10Mg cellular lattice structure was carried. Findings: Greater than 99% relative density can be achieved for different strut size when optimal process parameters are used. In the optimized process interval, the struts with a tilt angle of 10° can still be formed well, which is higher than the design limit of the inclined angle given in the related literature. The tilt angle has a significant effect on the surface roughness of the strut. The microhardness reached to 157 ± 3 HV, and the maximum compressive strength was 58.86 MPa, with the optimal process parameters. Originality/value: In this study, the characteristics such as the density, up-skin and down-skin roughness and dimensional accuracy of SLMed AlSi10Mg cellular lattice structure were carried. With the optimal geometric parameters, the authors tested microhardness and compressive strength of the cellular lattice structure. The results of this study provide theoretical and experimental basis for the realization of high-quality manufacturing and optimization design of aluminum alloy cellular lattice structure, which will meet more diversified industrial needs.